2015
DOI: 10.1115/1.4029552
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Plasticity Analysis of Stress Partitioning Mechanisms and Their Microstructural Dependence in Advanced Steels

Abstract: Two-phase advanced steels have an optimized combination o f high yield strength and large elongation strain at failure, as a result o f stress partitioning between a hard phase (martensite) and a ductile phase (ferrite or austenite). Provided with strong interfaces between the constituent phases, the failure in the brittle martensite phase will be delayed by the surrounding geometric constraints, while the rule o f mixture will dictate a targe strength of the composite. To this end, the microstructural design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Toy et al [75] found that quartz crystallographic orientations developed in early deformation events controlled which slip systems were activated during subse-quent deformation and, thus, whether or not the early fabric was preserved or overprinted. Preferential deformation due to crystal orientation has been shown to occur in peridotite [76], metallurgical samples [77], and deforming ice. For example, polycrystalline aggregates of ice, which is also in the hexagonal crystal system and is generally accepted to deform analogously to quartz, undergo preferential deformation of easy glide-orientated crystals in glaciers [78,79].…”
Section: Origin Of Cl-mottledmentioning
confidence: 99%
“…Toy et al [75] found that quartz crystallographic orientations developed in early deformation events controlled which slip systems were activated during subse-quent deformation and, thus, whether or not the early fabric was preserved or overprinted. Preferential deformation due to crystal orientation has been shown to occur in peridotite [76], metallurgical samples [77], and deforming ice. For example, polycrystalline aggregates of ice, which is also in the hexagonal crystal system and is generally accepted to deform analogously to quartz, undergo preferential deformation of easy glide-orientated crystals in glaciers [78,79].…”
Section: Origin Of Cl-mottledmentioning
confidence: 99%
“…Multiscale methods have a wide range of applications in material science. Many materials have the heterogeneous structures in nature or by fabrication, such as cement and concrete [37,46], crystalline alloys [18,36], bulk metallic glasses [17,29,47,48], shape memory composites [12,20,63] and reinforced polymers [19,67,68]. Cementitious materials can be modeled as lattice elements that consist of unhydrated cement and hydration products [49,56]; Cohesive zone model has been extensively applied to investigate the failure mechanism of alloys [26-28, 66, 69]; Modern homogenization techniques have been developed to study random composites [15,35,38] as well as heterogeneous materials such as biological tissues [30] and Neo-Hookean-type composites [23,54,65] with large deformations.…”
Section: Applications and Future Challengesmentioning
confidence: 99%
“…The abnormal behavior has been well explained by the mechanism of strain partitioning during the deformation of multilayered steel2223. And the failure of brittle martensite in the brittle/ductile multilayered steels has been delayed by the surrounding ductile phase242526. Therefore, the direct visualization of strain evolution is useful to understand the deformation mechanism of layered composites.…”
mentioning
confidence: 99%